การศึกษาสมรรถนะของพยาบาลวิชาชีพในหน่วยงานกุมารเวชกรรม โรงพยาบาลตติยภูมิ - วรันธิยา เฝ้าทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this research was to study of professional nurses’ competency in pediatric unit, tertiary hospitals. The sample consisted of 547 professional nurses in 28 tertiary hospitals who had at least 5 years experience in pediatric unit. Rating scale questionnaire was use to study professional nurses’ competency in pediatric unit. The content validity were establizhed by 5 experts. The reliability of the questionnaire, calculated by the Cronbach’s alpha coefficient, was .91. The data was analyzed using Principal Components Extraction and Orthogonal Rotation with Varimax Methhod The results were as follows: The of factor analysis of professional nurses’ competency in pediatric unit, tertiary hospitals yielded 7 factors which were by 74 items, accounted for 73.58 percent of total variance, and named as follows: 1. Nursing quality improvement competency, by 18 items which accounted for 14.50 percent of total variance. 2. Nursing knowledge integration competency, by 15 items which accounted for 11.54 percent of total variance. 3. Nursing of critical care, by 9 items which accounted for 11.20 of total variance. 4. Research and technology utilization competency, by 6 items which accounted for 10.56 percent of total variance. 5. Ethics and patient advocacy competency, by 10 items which accounted for 9.77 percent of total variance. 6. Communication competency, by 9 items which accounted for 8.98 percent of total variance. 7. Holistic pediatric care competency, by 7 items which accounted for 7.01 percent of total variance.